Changes in the physical capacity of road cyclists during the preparatory period - Byzdra, Krzysztof; Więckowski, Kamil; Piątek, Mirosław; Mikołajczyk, Janusz; Stępniak, Robert (Journal of Education, Health and Sport, 2017)
Graduation work entitled "Changes in the physical capacity of road cyclists during the preparatory period" is based on spiroergometric tests, which assess at the same time three systems: respiratory, circulatory and muscular. The work shows the changes effort possibilities of road cyclists, under the influence of training conducted during the preparatory period. In the theoretical part of this work were characterized the concept of physical capacity, its division and assessment methods of capacity. Selected parameters were presented, determined in the spiroergometric tests. Also the time structure of training in road cycling was described. Each of competitors were tested twice a time. The first test took place at the turn of January and December, that is during the preparatory period. The second test cyclists took place in the second half of March, so at the end of the preparatory period, before the first races. The results of five parameters were analyzed: WR max, WR (VT1), VO2max, VO2 / HR (VT1),% VO2max (VT1). All tested parameters were increased during preparatory period. The most susceptible to the increase parameters under the influence of training during the preparatory period are: power generated on the anaerobic threshold and on the top of the effort (increase 12,68% and 11,25%), oxygen pulse (12,88%). Training improve the work of the muscular and circulatory systems. The least exposed to changes are parameters of gas exchange. Spiroergometric tests results can be used for planning training in subsequent training periods.